PENDAMPINGAN E-FINANCE BUSINESS PADA PRODUSEN KAMPUNG KUE RUNGKUT SURABAYA - Ekaningtias, Dyah; Supriyati, Supriyati; Nurhadi, Nurhadi (Jurnal Ipteks Akuntansi Bagi Masyarakat, 2021)
Kampung Kue Rungkut Surabaya is one of the icons of the city of Surabaya and as a culinary center that has been developed after the monetary crisis in 1998. Business management is not good, financial management and human resources are poorly planned, and bookkeeping administration support is also not available so they are not able to assess their business performance. In real terms and unable to predict future business conditions. Community service activities are carried out using two methods, namely training and business assistance. The e-business-based business management training was aimed at cake producers and the younger generation, which was attended by 24 active members of the cake village community. This training has succeeded in providing insight, especially for the younger generation, that business is not only focused on production, but requires strategy and technology adaptation in business, known as business digital (e-business). Next is mentoring activities that are not just observations, but the implementation team tries to help create business development towards e-business. The results of the training and assistance in the form of increasing the role of the younger generation, increasing the understanding of members of the village cake community, improving the administration of the community, developing business information systems, compiling simple reports. Community service activities also received support from the Surabaya City Cooperatives and UMKM Service and BPR Artha Unggul Surabaya. The potential and condition of the Kampung Kue Rungkut Surabaya still has hope to be developed. Therefore, the possibility of development carried out by the implementing team with partners is to conduct trials to the implementation of e-business in order to be able to improve the people's economy as before the COVID-19 pandemic and make Kampung Kue a culinary and educational tourism village in the city of Surabaya